Pengaruh Metode Diskusi Kelompok dalam Pembelajaran Menulis Teks Berita oleh Siswa Kelas VIII SMP Negeri 7 Pematangsiantar - Dea Renita Saragih; Jumaria Sirait; Martua Reynhat Sitanggang Gusar (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
This study aims to determine: (1) the ability of students to write news texts before using the group discussion method in class VIII of SMP Negeri 7 Pematangsiantar, (2) the ability of students to write news texts after using the group discussion method in class VIII of SMP Negeri 7 Pematangsiantar and, ( 3) The effect of the group discussion method on the ability to write news texts by class VIII students of SMP Negeri 7 Pematangsiantar. This type of research includes pre-experimental research with one group pre-test post-tst design research (Sugiyono, 2019:74), the reason the researcher chooses Pre-experimental research is because this study aims to determine the effect of using group discussion methods in learning to write news texts by VIII grade students of SMP Negeri 7 Pematangsiantar. The results of this study are: (1) the results of the initial test ability (pre-test) in the skills of writing news texts for class VIII-6 SMP Negeri 7 students before the group discussion method is applied, the average score is 66.40. While the results of the final text ability (post-test) after the group discussion method was applied, the average value was 73.12. (2) The results of the score on the assessment aspect of writing news texts before applying the group discussion method obtained the highest score in the vocabulary assessment aspect which amounted to 760 with an average of 23.75 while the lowest assessment aspect was found in the organizational assessment aspect, which amounted to 320 with an average 10. After applying the group discussion method whose value increased, the highest assessment aspect of writing news texts was found in the content aspect, which amounted to 720 with an average of 22.5, while the lowest assessment aspect was found in the mechanical aspect, which amounted to 310 with an average of 9.68. (3) The analysis has been carried out and has been tested statistically. That th is greater than tt (6.72>1.78) causes H0 to be rejected and Ha to be accepted. Thus, it can be concluded that there is an effect of group discussion method on news text writing skills by students of class VIII-6 SMP Negeri 7 Pematangsiantar.